Effects of vegetation management intensity on biodiversity and ecosystem services in vineyards: A meta‐analysis. Issue 5 (4th March 2018) - Winter, Silvia; Bauer, Thomas; Strauss, Peter; Kratschmer, Sophie; Paredes, Daniel; Popescu, Daniela; Landa, Blanca; Guzmán, Gema; Gómez, José A.; Guernion, Muriel; Zaller, Johann G.; Batáry, Péter
Abstract: At the global scale, vineyards are usually managed intensively to optimize wine production without considering possible negative impacts on biodiversity and ecosystem services (ES) such as high soil erosion rates, degradation of soil fertility or contamination of groundwater. Winegrowers regulate competition for water and nutrients between the vines and inter‐row vegetation by tilling, mulching and/or herbicide application. Strategies for more sustainable viticulture recommend maintaining vegetation cover in inter‐rows, however, there is a lack of knowledge as to what extent this less intensive inter‐row management affects biodiversity and associated ES. We performed a hierarchical meta‐analysis to quantify the effects of extensive vineyard inter‐row vegetation management in comparison to more intensive management (like soil tillage or herbicide use) on biodiversity and ES from 74 studies covering four continents and 13 wine‐producing countries. Overall, extensive vegetation management increased above‐ and below‐ground biodiversity and ecosystem service provision by 20% in comparison to intensive management. Organic management together with management without herbicides showed a stronger positive effect on ES and biodiversity provision than inter‐row soil tillage. Soil loss parameters showed the largest positive response to inter‐row vegetation cover. The second highest positive response was observed for biodiversity variables, followed by carbon sequestration, pest control and soil fertility. We found no trade‐off between grape yield and quality vs. biodiversity or other ES. Synthesis and applications . Our meta‐analysis concludes that vegetation cover in inter‐rows contributes to biodiversity conservation and provides multiple ecosystem services. However, in drier climates grape yield might decrease without irrigation and careful vegetation management. Agri‐environmental policies should therefore focus on granting subsidies for the establishment of locally adapted diverse vegetation cover in vineyard inter‐rows. Future studies should focus on analysing the combined effects of local vineyard management and landscape composition and advance research in wine‐growing regions in Asia and in the southern hemisphere. Abstract : Our meta‐analysis concludes that vegetation cover in inter‐rows contributes to biodiversity conservation and provides multiple ecosystem services. However, in drier climates grape yield might decrease without irrigation and careful vegetation management. Agri‐environmental policies should therefore focus on granting subsidies for the establishment of locally adapted diverse vegetation cover in vineyard inter‐rows. Future studies should focus on analysing the combined effects of local vineyard management and landscape composition and advance research in wine‐growing regions in Asia and in the southern hemisphere.